(untitled) - Peter Fellows (Rome, 1997)
This book is intended to assist planners and field workers who involved in the promotion of small scale fruit and vegetable processing in developing countries. It sets out the different reasons why food processing may be important for improved nutrition and food security; for employment and income generation
Keywords: food conservation,food supply